Analytical truss model with an extended strut for conventionally reinforced concrete coupling beams with span-to-height ratios larger than 1.75. (1st August 2022) - Zhou, Ke-Jing; Chen, Hui; Yi, Wei-Jian
Highlights: A truss model with a novel extended strut is developed. The model predicts the shear strength of 23 NSCBs with a high accuracy. The model well predicts the skeleton curves of 17 NSCBs. A simplified model is proposed for engineering applications. A standardized design method is developed to indirectly consider the deformation. Abstract: Conventionally reinforced concrete coupling beams are widely used in coupled shear wall structures to improve the structural lateral stiffness and energy dissipation capacity. Therefore, it is of great significance to develop a simple mechanical analytical model that can accurately predict the shear strength and deformation of conventionally reinforced concrete coupling beams. In the previous work, the authors proposed an analytical truss model for coupling beams with the span-to-height ratio l / h  ≤ 1.75. However, due to the changes in the load-transfer mechanism, the model is not suitable for coupling beams with l / h  > 1.75. By comparing existing test results of coupling beams with different span-to-height ratios and numerical results provided by a refined finite element simulation, the evolution of the load-transfer mechanism with the variation of l / h is identified. On this basis, an analytical truss model that is consist of a novel extended strut and several secondary conventional struts is proposed. The proposed model is verified to predict the shear strength of 23 existing coupling beams well, with l / h  > 1.75, and the coefficient of variation (COV) is of 0.092. In contrast, the design codes ACI 318–19 and GB 50010–2010 provide less accurate predictions (their COVs are 0.263 and 0.195, respectively). Moreover, the calculated shear force-transverse displacement skeleton curves using the proposed model are in good agreement with the test results. On the other hand, by simplifying the calculation process of this model, a simplified model is put forward for practical engineering application, resulting in a slight loss of accuracy (the COV is 0.109). In order to prevent the insufficient ductility of coupling beams with l / h  > 1.75 with this simplified model, a standardized design method is also proposed.